Preliminary Assessment of TVET Integration in Early Preschool Science Education Through The Farm-to-Table Approach - Zainal Abidin, Muhamad Nazarwin; Abd Wahid, Muhammad Zakwan Anas; Roslin, Emir Azreen; Kamaruzaman, Siti Khadijah; Shahrol Saidi, Aiman Fikri (Online Journal for TVET Practitioners, 2025)
Planting seeds in young minds goes beyond textbooks, it thrives in soil, sunlight, and hands-on experience. This study explores the effectiveness of the Farm-to-Table approach in enhancing preschoolers’ understanding of agriculture through experiential learning aligned with the Early Science (SA 3.4) curriculum and Technical and Vocational Education and Training (TVET) principles. Using a mixed-methods design, 30 preschool children aged 5–6 were assessed through pre- and post-assessment, structured observations, interviews, and task-based evaluations. Results showed a significant increase in post-assessment scores from a mean of 52.00 to 76.83 (t = –14.02, p = 0.008), indicating a 47.7% improvement in agricultural knowledge. Memory reinforcement also rose by 19.18% (t = 8.03, p < 0.001), suggesting enhanced retention and understanding. Furthermore, 90% of the students demonstrated measurable improvements in fine and gross motor skills, as confirmed by Wilcoxon Signed-Rank Test results (Z = –4.10 and –4.21, p < 0.001). Additionally, 85% showed improved classroom collaboration, communication, and teamwork during activities. These findings confirm that the Farm-to-Table approach, when combined with gamification and technical elements, fosters cognitive, physical, and social development. By bridging theoretical knowledge with real-world experiences, this approach not only supports curriculum goals but also prepares children with essential life skills, setting a strong foundation for lifelong learning and holistic growth.